Cybersecurity Threats and Best Practices of Working from Home - Syed Faisal, Syarifah Hanan; Ismail, Fadillah (Journal of Techno-Social, 2022)
The concept of working from home encouraged in limiting movement due to the transmission of COVID-19 is not a new culture. In this era of pandemics, this has become a new norm for almost all sectors of employment. The concept of working from home demands the use of digital equipment and internet services. With this situation, it exposes employees to cyber security risks to themselves and the organization or employer. According to Cyber Security Malaysia (CSM), a total of 4,596 reports were made on cybercrime cases, earlier this year until April. therefore, this paper will examine the effects of working from home and the threats of cybercrime as well as possible solutions.